Chronic peroxisome proliferator-activated receptorβ/δ agonist GW0742 prevents hypertension, vascular inflammatory and oxidative status, and endothelial dysfunction in diet-induced obesity. Issue 9 (September 2015) - Toral, Marta; Gómez-Guzmán, Manuel; Jiménez, Rosario; Romero, Miguel; Zarzuelo, María José; Utrilla, María Pilar; Hermenegildo, Carlos; Cogolludo, Ángel; Pérez-Vizcaíno, Francisco; Gálvez, Julio; Duarte, Juan
Abstract : Objective: Endothelial dysfunction plays a key role in obesity-induced risk of cardiovascular disease. The aim of the present study was to analyze the effect of chronic peroxisome proliferator-activated receptor (PPAR)β/δ agonist GW0742 treatment on endothelial function in obese mice fed a high-fat diet (HFD). Methods and results: Five-week-old male mice were allocated to one of the following groups: control, control-treated (GW0742, 3 mg/kg per day, by oral gavage), HFD, HFD + GW0742, HFD + GSK0660 (1 mg/kg/day, intraperitoneal) or HFD-GW0742-GSK0660 and followed for 11 or 13 weeks. GW0742 administration to mice fed HFD prevented the gain of body weight, heart and kidney hypertrophy, and fat accumulation. The increase in plasma levels of fasting glucose, glucose tolerance test, homeostatic model assessment of insulin resistance, and triglyceride found in the HFD group was suppressed by GW0742. This agonist increased plasma HDL in HFD-fed mice and restored the levels of tumor necrosis factor-α and adiponectin in fat. GW0742 prevented the impaired nitric oxide-dependent vasodilatation induced by acetylcholine in aortic rings from mice fed HFD. Moreover, GW0742 increased both aortic Akt and endothelial nitric oxide synthase phosphorylation, and inhibited the increase in caveolin-1/endothelial nitric oxide synthase interaction, ethidium fluorescence, NOX-1, Toll-like receptor 4, tumor necrosis factor-α, and interleukin-6 expression, and IκBα phosphorylation found in aortae from the HFD group. GSK0660 prevented all changes induced by GW0742. Conclusion: PPARβ/δ activation prevents obesity and exerts protective effects on hypertension and on the early manifestations of atherosclerosis, that is, endothelial dysfunction and the vascular pro-oxidant and pro-inflammatory status, in HFD-fed mice. Abstract : Supplemental Digital Content is available in the text